A Remarkable Response of Granulomatous Hypophysitis to Infliximab in a Patient With a Background of Crohn's Disease—A Case Report - Force, Bahar K.; Vogel, Tiphanie P.; Nguyen, Dang M.; Heck, Kent A.; Sebastian, Sherly; Takashima, Mas; Yoshor, Daniel; Samson, Susan L. (Frontiers in Endocrinology, 2020)
Background: There are four histologic types of hypophysitis - lymphocytic, granulomatous, xanthomatous or IgG4-related. Granulomatous hypophysitis is the second most common form and is characterized by multinucleated giant cells with granulomas and histiocytes. It can be idiopathic or secondary to another process such as infection, sarcoidosis, vasculitis, dendritic cell disorders, Crohn’s disease (CD) or a reaction to rupture of a Rathke’s cyst or pituitary adenoma. We present a case of granulomatous hypophysitis in a patient with CD who had resistance to corticosteroids but a dramatic response to immunosuppressive therapy with anti-tumor necrosis factor (TNF)-alpha therapy. Case description: A 43-year-old woman with a 9-year history of ileal and colonic CD presented to the Pituitary Center with headaches, visual disturbance, fatigue, nausea and secondary amenorrhea. She was not on active therapy for her CD at the time of presentation and had no gastrointestinal symptoms. Hormonal evaluation revealed hyperprolactinemia, secondary hypothyroidism and adrenal insufficiency. MRI revealed a 12 x 12 x 19 mm sellar lesion abutting the optic chiasm, reported as a macroadenoma. The patient underwent endoscopic transsphenoidal biopsy of the pituitary mass. Pathology revealed granulomatous hypophysitis. Evaluation for secondary causes of hypophysitis was negative. Despite a course of high dose prednisone, her symptoms and MRI findings worsened and she developed diabetes insipidus. Using a personalized medicine approach, she was started on anti-TNF-alpha therapy with infliximab combined with azathioprine, which are indicated for treatment of CD. Her headaches and diabetes insipidus resolved and her menstrual cycles resumed. MRI at 3 months and more than 1.5 years after initiation of anti-TNF-alpha therapy revealed durable resolution of the pituitary mass. Conclusion: To our knowledge, this is the first reported case of successful use of anti-TNF-alpha therapy in a patient with granulomatous hypophysitis. Although glucocorticoids are used as first-line therapy for hypophysitis, granulomatous hypophysitis can be corticosteroid resistant and other immunosuppressive approaches may be needed. Our case illustrates that anti-TNF-alpha agents can be used for granulomatous hypophysitis to achieve a swift and sustainable resolution of pituitary inflammation.